The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1073/pnas.1615669114
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm judgments reveal a frequency asymmetry in the perception and neural coding of sound synchrony

Abstract: In modern Western music, melody is commonly conveyed by pitch changes in the highest-register voice, whereas meter or rhythm is often carried by instruments with lower pitches. An intriguing and recently suggested possibility is that the custom of assigning rhythmic functions to lower-pitch instruments may have emerged because of fundamental properties of the auditory system that result in superior time encoding for low pitches. Here we compare rhythm and synchrony perception between low-and high-frequency ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Greater sensitivity to the temporal misalignment of low tones was observed when they were presented earlier than expected, which suggested better time encoding for low sounds. These results were replicated and extended by Wojtczak et al ( 13 ), who showed that the effect was related to greater tolerance for low-frequency sounds lagging high-frequency sounds than vice versa. However, these studies only provide indirect evidence for the effect of low sounds on internal entrainment to rhythm, inferred from brain responses to deviant sounds.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Greater sensitivity to the temporal misalignment of low tones was observed when they were presented earlier than expected, which suggested better time encoding for low sounds. These results were replicated and extended by Wojtczak et al ( 13 ), who showed that the effect was related to greater tolerance for low-frequency sounds lagging high-frequency sounds than vice versa. However, these studies only provide indirect evidence for the effect of low sounds on internal entrainment to rhythm, inferred from brain responses to deviant sounds.…”
supporting
confidence: 64%
“…There has been a recent debate as to whether evolutionarily shaped properties of the auditory system lead to superior temporal encoding for bass sounds ( 12 , 13 ). One study using electroencephalography (EEG) recorded brain responses elicited by misaligned tone onsets in an isochronous sequence of simultaneous low- and high-pitched tones ( 12 ).…”
mentioning
confidence: 99%
“…This bias provides a potential neurobiological reason for why low-frequency instruments carry the beat in some music (for example see Snyder and Krumhansl, 2001 ). However, it is tricky to test this perceptually; multiple instruments often play simultaneously on the beat, and cochlear delays can explain biases for simultaneous events (Wojtczak et al, 2017 ). Our stimuli used amplitude modulations at distinct tempi and phases to reduce the effects of simultaneous events, and we quantified the bias using the synchronization strength of neural activity rather than timing to specific events.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects also identify beats in piano ragtime music better when the left hand (lower frequency) is played alone than when the right hand (higher frequency) is played alone, although this could be due to the regularity of the left hand for this type of music (Snyder and Krumhansl, 2001 ). A low-frequency bias for beat timing could result from cochlear processing, where low frequencies cause a greater spread of excitation than higher frequencies (Hove et al, 2014 ), but these effects need to be disambiguated from cochlear delays that can produce similar biasing effects for simultaneous events (Wojtczak et al, 2017 ). For repeating “frozen” noise, where the noise signal was identical on each repetition, subjects focus on mid-frequency perturbations in the signal, between 300 and 2,000 Hz, when tapping along with the repetition (Kaernbach, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, recent models have been proposed to quantify the extent to which beat perception could be explained by early auditory sensory processing in brainstem auditory nuclei that we share with other animals (Rajendran et al ., ). This hypothesis is also related to a line of research investigating the extent to which musical conventions and habits are determined by evolutionarily shaped human physiology (Hove et al ., ; Merchant & Honing, ; Wojtczak et al ., ).…”
Section: Introductionmentioning
confidence: 97%